Delayed Diagnosis of Wilson's Disease Report From 179 Newly Diagnosed Cases in China - Yu, Minling; Ren, Linxiang; Zheng, Muxin; Hong, Mingfan; Wei, Zhisheng (Frontiers in Neurology, 2022)
Objective To analyze the initial symptom and the cause of the misdiagnosis of Wilson's Disease (WD) so as to enhance awareness of this condition and reduce diagnostic errors. Methods The clinical data of 179 patients with the confirmed diagnosis of WD who were hospitalized in the First Affiliated Hospital of Guangdong Pharmaceutical University from October 2014 to September 2021 were analyzed. Those patients who had attended two or more hospitals, had been misdiagnosed as other diseases, or failed to get a clear diagnosis for 3 months and over before hospitalization were included in the group of clinical misdiagnosis or the group without a definite diagnosis. Results One hundred twenty-nine cases (72.1%) were misdiagnosed, 39 cases (21.8%) failed to be diagnosed as a specific disease, and only 11 cases (6.2%) had been diagnosed as WD within 3 months at the early stage of the disease. WD was easily masqueraded as a variety of diseases, including all types of hepatitis, cirrhosis, splenomegaly, hepatomegaly, encephalitis, encephalopathy, peripheral neuropathy, psychosis, osteoarthrosis, nephrosis, anemia, and other illnesses. Conclusion Wilson's Disease is prone to long-term misdiagnosis or unclear diagnosis. Early diagnosis and treatment are the most important determinations of the prognosis. Therefore, when facing patients with doubtful WD, it is valued to perform Kayser–Fleischer ring, copper metabolism, imaging examination, genetic tests, and radioactive copper test if necessary.